What was justice in Ancient times? Misharum, Mishpat and Diké: different words to refer to reciprocity in social relations - Aguillaume Gandasegui, Guillermo (DERECHOS Y LIBERTADES: Revista de Filosofía del Derecho y derechos humanos, 2026)
In this paper, I analyse the conceptions of Justice in ancient Mesopotamia, the Old Testament, and Archaic Greece to seek a common substrate among the three, and I believe it can be found in the principle of reciprocity. Next, I explain how reciprocity is a mechanism for maintaining social cooperation, whose functioning is supported by Game Theory, Anthropology, and even Primatology. I will try to explain the importance this principle takes on in complex urban societies and how it is used in modern theories of Justice to, finally, approach its usefulness in defining the very idea of Justice.
Keywords: Justice; ancient Law; reciprocity; Anthropology; cooperation